The monotheism of actions (tawhid al-af‘al) in the works by Abd Al-Rahman Jami - Andrey Lukashev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The thesis that God is the only active agent is not less important for Islamic monotheism then the declaration of His unity. It rises the question of the human actions’ status as well. The difference between divine and human actions in the Islamic thought has historical, philosophical, theological, and ethical significance. Abd al-Rahman Jami is one of the most prominent Naqshbandi Sufis. The Naqshbandi tariqat is widely spread in Central Asia, the Ural-Volga region, at the North Caucasus and ets. The author is an outstanding Sufi Persian poet of the classical period. His heritage can be regarded as a continuation of the classical Persian Sufi didactic tradition, which includes the works by such mystics as Sanai, Attar, and Rumi. He was also an admirer of the Ibn Arabi (a prominent Andalusian thinker) philosophy and was very well aware of the al-Suhrawardi’s (the Ishraqism founder) heritage. Of course, he was very well familiar with the classical philosophy. The synthesis of all these diverse lines of thought is evident in Jami’s understanding of the actions metaphysics. On one hand, Jami speaks of the God as the sole creator and the source of all actions. On the other hand, he insists on the human actions’ reality; moreover, from his point of view, humans possess freedom of choice. The conflict between the assertion of the divine might absoluteness and the consequent predestination of all human actions by divine will, on one hand, and the declaration of human freedom of choice, on the other, is resolved by Jami through the assertion that humans are predetermined by God to perfection. The fully realized Perfect Man’s freedom of choice is identical to the divine choice, directed to the good. Any other choice of a human is not completely free but determined, for example, by a passionate soul that leads him to evil. Jami understands the God, the highest level of being, and treats Him in this regard not so much as an actor but as the action itself. Following Ibn Arabi, Jami also identifies divine selfhood with being (wujud). Thus, it can be logically concluded, that Jami equates being (wujud) and action, offering some kind of the "being" processual interpretation, that can be partly traced back to the classical philosophy heritage, translated later by the falasifa (eg. Ibn Sina).